Role of [18F]-fluoro-2-deoxy-D-glucose positron emission tomography in early and late therapy assessment of patients with advanced Hodgkin lymphoma treated with bleomycin, etoposide, adriamycin, cyclophosphamide, vincristine, procarbazine and prednisone - Markova, Jana; Kahraman, Deniz; Kobe, Carsten; Skopalova, Magdalena; Mocikova, Heidi; Klaskova, Katerina; Dedeckova, Katerina; Eich, Hans-Theodor; Böll, Boris; Dietlein, Markus; Kozak, Tomas (Leukemia & lymphoma, 2012)
The prognostic value of positron emission tomography (PET) in early therapy response assessment, after completion of chemotherapy and 3 months after the end of treatment in advanced Hodgkin lymphoma (HL) remains to be defined. We report the results of 69 patients with first presentation of advanced HL. [18F]-fluoro-2-deoxy-d-glucose (FDG)-PET scan was performed after four cycles (PET-4), on completion of chemotherapy after 6/8 cycles (PET-6/8) and 3 months after the completion of chemotherapy (PET 3-months). Median follow-up was 55 months. The negative predictive value (NPV) for PET-4, PET-6/8 and PET 3-months was 98%, 95% and 97%, respectively. The 4-year progression-free survival (PFS) for PET-4 negative (n = 51) and PET-4 positive (n = 18) patients was 96% and 78%, respectively (p = 0.016). The 4-year PFS for PET-6/8 negative (n = 59) and PET-6/8 positive (n = 9) patients was 95% and 78%, respectively (p = 0.046). Patients with a large mediastinal mass constituted nearly all of the PET-4 positive (16/18) and PET-6/8 positive (8/9) patients. After radiotherapy of PET-6/8 positive patients, PET 3-months was negative in 64 (97%) and positive in two (3%) patients. PET 3-months after the end of chemotherapy was of limited value when the interim PET-4 was negative. Interim PET after four cycles of bleomycin, etoposide, adriamycin, cyclophosphamide, vincristine, procarbazine and prednisone (BEACOPP) is a strong prognostic marker for PFS in advanced HL.
Keywords: výsledek terapie; Young Adult; doxorubicin; Male; Antineoplastic Combined Chemotherapy Protocols; mladý dospělý; následné studie; Adolescent; Cyclophosphamide; prognóza; Drug Administration Schedule; prokarbazin; Kaplan-Meier Estimate; Radiopharmaceuticals; Positron-Emission Tomography; pozitronová emisní tomografie; Adult; Kaplanův-Meierův odhad; Vincristine; dospělí; etoposid; mužské pohlaví; mladiství; Follow-Up Studies; Hodgkin Disease; Treatment Outcome; Time Factors; prednison; bleomycin; fluorodeoxyglukosa F18; radiofarmaka; Procarbazine; lidé; Etoposide; ženské pohlaví; Fluorodeoxyglucose F18; Humans; protokoly protinádorové kombinované chemoterapie; časové faktory; cyklofosfamid; Hodgkinova nemoc; Bleomycin; Prednisone; Prognosis; rozvrh dávkování léků; Female; lidé středního věku; Doxorubicin; vinkristin; Middle Aged